The Role of Organizational Support in Health Program Implementation - Hasanbasri, Mubasysyir; Jaladara, Vena (BKM Public Health and Community Medicine, 2024)
Purpose: Delays in improving public health are closely related to the population's social and economic issues. These delays are also linked to various obstacles in implementing programs that have been proven effective in other countries. Some improvements in overcoming these barriers have occurred related to the support for field activities. This research characterizes the five organizational elements used to implement essential health programs in Indonesia. Methods: We used the five organizational elements framework, which emphasizes the roles of service delivery, frontline workers, support systems, and program managers. Findings: The clarity in contracts for program managers is often seen as a clarity in administrative functions rather than a focus on problem-solving functions within the community. This understanding is crucial for devising effective strategies for program implementation. Moreover, there is an urgent need to strengthen the support system functions that assist frontline workers, a critical step in ensuring the smooth execution of health programs. Conclusion: The success of health programs is intricately tied to the effectiveness of program managers. It is not just a role but a crucial responsibility for community health centers (Puskesmas) to adopt an internal worker contract approach for program managers. Furthermore, program managers should operate under a contract as leaders for frontline workers and support systems, underscoring their pivotal role in the process.